Comparative Analysis of Digital Competence Education Based on the DigCompEdu Framework in Indonesian and Chinese Higher Education - Dendy maulana yusuf; Grace Tofer Claudius Close One Prinsen Wahyudiono; Alya Na’imatur Rosyidah; Faila Sufa Arum Agustina; Ratna Tri Hikmatus Zurro; Muhammad Fajar Wahyudi Rahman (Universitas Negeri Surabaya, 2026)
Given the growing importance of digital competence in education, this paper provides a comparative analysis of DigCompEdu-based digital competence education practices in higher education in Indonesia and China. This study uses a systematic literature review combined with policy document analysis to establish how both countries implement digital competence frameworks for educators. Data sources include indexed journal articles and official documents meeting specific criteria related to higher education, lecturers, and DigCompEdu frameworks. The results show that in Indonesia, DigCompEdu is more widely adopted at research and study program levels, particularly in teacher training institutions, while in China, it functions primarily as a normative framework at policy levels. In both countries, relatively strong competency areas include digital resources usage, communication, collaboration, and security, whereas digital assessment, reflective practice, and learner empowerment remain weak. This study recommends developing standardized instruments and explicitly integrating DigCompEdu areas into higher education curricula.